(untitled) (Agroindustrial Science, 2026)
This study analyzes how Artificial Intelligence is transforming logistics efficiency and exports in the agribusiness sector. Through a systematic review of scientific literature (2020–2025) and a bibliometric analysis using Scopus data, technologies such as Machine Learning, Deep Learning, IoT, and blockchain are identified, which are improving traceability, demand prediction, and sustainability in the agri-food chain. The results show that countries such as China, India, and the United States lead scientific production in this field, while regions such as South America face limitations due to a lack of technological infrastructure. Artificial Intelligence applications range from real-time monitoring and quality control to crop prediction and loss reduction. The study concludes that Artificial Intelligence strengthens the competitiveness of the agribusiness sector in international markets. Developing countries are encouraged to invest in digital infrastructure, promote local research, and train personnel to close technological gaps.